Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Video Interaktif terhadap Hasil Belajar Mata Pelajaran Projek Kreatif dan Kewirausahaan di SMK PGRI 3 Badung - I Made Ardita; I Made Yudana; Kadek Rihendra Dantes (LP. Ma'arif Janggan Magetan, 2023)
This study aims to 1) find out the differences in learning outcomes of creative and entrepreneurial project subjects before applying the interactive video media-assisted problem-based learning model, 2) knowing the differences in learning outcomes of creative and entrepreneurial project subjects after applying the problem-based learning model assisted by interactive video media, 3) knowing the significant influence of the problem-based learning model assisted by video media interactive for grade XI students majoring in Hospitality at SMK PGRI 3 Badung in 2023/2024. This research is quantitative research with a type of research, namely quasi-experiment (quasy experiment). The results showed that: 1) The learning outcomes of creative and entrepreneurial project subjects before applying the interactive video media-assisted problem-based learning model were obtained a range value of 21, a minimum value of 56 and a maximum value of 77, at a mean value of 66.59, a standard deviation of 6.265 and a variance of 39.248, 2) Student learning outcomes after applying a problem-based learning model assisted by video media interactive where the range value is 12, at a minimum value of 80 and a maximum of 92, the mean value is 85.97, the standard deviation is 3.262 and the variance value is 10.638, 3) There is an influence of the problem-based learning model assisted by interactive video media on the results of student learning creative and entrepreneurial project subjects where Pair 1 obtained a significance value (2-tailed) of 0.000 smaller than 0.05, then it means that there is a difference in the average learning outcomes of students for the experimental class Pre-Test with the experimental class Post-Test. In the output of Pair 2 obtained a significance (2-tailed) of 0.000 smaller than 0.05, so it means that there is a difference in the average learning outcomes of students for the control class Pre-Test with the control class Post-Test.